Effects of kneading machine type and total element revolutions on dough rheology and bread characteristics: A focus on straight dough and indirect (biga) methods. (January 2022) - Venturi, Manuel; Cappelli, Alessio; Pini, Niccolò; Galli, Viola; Lupori, Lucrezia; Granchi, Lisa; Cini, Enrico
Abstract: Kneading (or mixing) is a fundamental unit operation which must be carefully managed since it significantly influences the development of the gluten network and the final bread quality. Nevertheless, there is a lack of specific researches regarding kneading machine type and total element revolutions, thus motivating this work. This paper assesses differences in dough rheology and bread characteristics as a function of two factors: kneading machine type (spiral and double-arm) and total element revolutions (800, 1600, and 2400). Two breadmaking methods, namely straight dough and biga, were investigated. Results show that kneading machine type and total element revolution have statistically-significant effects on dough rheology and bread characteristics in both the methods. For straight dough method, double-arm mixer seems to be the most suitable for the production of bread with optimal characteristics. On the other hand, for biga method, spiral mixer was able to produce bread with the highest specific volume and loaf height. The results presented here allowed a big step forward in understanding the effects of kneading machine type and total element revolutions. Specifically, our work could guide the improvement of straight dough and biga methods (using double-arm and spiral mixers, respectively), and the development of specific kneading machines. Highlights: Effects of kneading machine type and total element revolutions were assessed. Impacts on dough rheology and bread characteristics were investigated. Two breadmaking methods (straight dough and biga ) were tested. For straight dough method, optimal breads were produced using a double-arm mixer. For biga method, instead, spiral mixer produced improved bread loaves.